Strategic Adaptation of Micro, Small, and Medium Enterprises (MSMEs) to Business Competition Regulation Dynamics - Melki T. Tunggati; Sri Olawaty Dj Suaib; Aurelia Laura Quartia Po’oe; Andriansyah Andriansyah (JURNAL AKTA, 2026)
This study aimed to analyze the strategic adaptation of Micro, Small, and Medium Enterprises (MSMEs) in responding to the dynamics of business competition regulations within the context of digital economic transformation, as well as to evaluate the effectiveness of these adaptation strategies. The research employed a normative-empirical legal research method with a juridical-sociological approach. Primary data were collected through in-depth interviews, observations, and focus group discussions involving MSME actors, government officials, and relevant stakeholders, while secondary data consisted of laws and regulations, academic journals, policy documents, and official reports. The collected data were analyzed qualitatively using a triangulation technique to ensure data validity and analytical depth. The novelty of this research lay in the formulation of an integrative adaptation strategy model for MSMEs, which combined regulatory intelligence, digital–traditional hybridization, resilient collaboration, and sustainable innovation as key pillars in addressing regulatory and competitive pressures. The findings demonstrated that, despite limited understanding of business competition regulations, MSMEs were able to maintain resilience and achieve business growth through adaptive strategies supported by a strong local ecosystem, including government support, digital infrastructure, and social capital. The study concluded that effective adaptation to business competition regulation dynamics required not only legal compliance but also the ability of MSMEs to integrate regulatory awareness with digital capability development and collaborative networks. These findings emphasized the importance of responsive and inclusive policy frameworks oriented toward MSME empowerment in order to create healthy, fair, and sustainable business competition in the digital era.